2017
DOI: 10.1371/journal.pone.0179348
|View full text |Cite
|
Sign up to set email alerts
|

The association between 38 previously reported polymorphisms and psoriasis in a Polish population: High predicative accuracy of a genetic risk score combining 16 loci

Abstract: ObjectivesTo confirm the association of previously discovered psoriasis (Ps) risk loci with the disease in a Polish population and to create predictive models based on the combination of these single nucleotide polymorphisms (SNPs).Material and methodsThirty-eight SNPs were genotyped in 480 Ps patients and 490 controls. Alleles distributions were compared between patients and controls, as well as between different Ps sub-phenotypes. The genetic risk score (GRS) was calculated to assess the cumulative risk conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 52 publications
1
40
0
Order By: Relevance
“…Therein, we found that the consuming significance probability level was 0.05 ( Table 1 ). The polygenic risk score was 38 SNP and was calculated according to Kisiel et al [ 15 ]. AUC values were calculated with the R-package “pROC” software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therein, we found that the consuming significance probability level was 0.05 ( Table 1 ). The polygenic risk score was 38 SNP and was calculated according to Kisiel et al [ 15 ]. AUC values were calculated with the R-package “pROC” software.…”
Section: Methodsmentioning
confidence: 99%
“…For populations of Caucasian origin, the AUC achieved 0.76 using 63 SNPs [ 13 ]. A recent study created a PV prediction GRS based on 38 highly associated SNP [ 15 ]. In this study, we used GRS to differentiate patients with severe and moderate-to severe PV from the general Russian population.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also noted that the same significant HCP5 SNV in psoriasis and HIV infections is not surprising since psoriasis can be triggered by infection with HIV and other viruses. Hence, it is possible that HCP5 - C carriers mount a strong immune reaction to viral infection, and when psoriasis is associated with other genes such as corneodesmosin, POU5F1, MICA , and HLA-C in the MHC and genes outside the MHC in genetically susceptible individuals [116], then this reaction might lead to excessive inflammation in skin and joints.…”
Section: Hcp5 Single Nucleotide Variant (Snv) Associations With DImentioning
confidence: 99%
“…Accordingly, genetic associations between psoriasis and IL‐17 pathway genes, including IL23R and the key signal transducer TRAF3IP2 (also called ACT1 ), have been reported. Nevertheless, the overall risk conferred by these variants remains moderate (mean OR: 1.98 for IL23R and 1.11 for TRAF3IP2 , respectively), and, despite acting as direct drug targets, no genetic association has been identified for IL17F , IL17A or IL17RA . It remains unclear whether the frequency of disruptive mutations in these genes is too low to have been detectable by existing studies.…”
Section: Introductionmentioning
confidence: 99%